COMPARISON OF THE EFFECTIVENESS OF CONTEXTUAL, PROBLEM SOLVING, AND SCIENTIFIK APPROACH OT COOPERATIF SETTING IN MATHEMATICS LEARNING OF CLASS VII STUDENTS AT SMPN ACCREDITATION A - Ahmad Syamsuadi; Muhammad Arif Tiro; Muhammad Darwis (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This study is experiment research, which aimsat examining the level of target achievement of students’ learning result taught by using contextual approach of cooperative setting, scientific approach of cooperative setting, and problem solving approach of cooperative setting based on (a) the posttest score of students, (b) improvement of students’ learning result, and examining the effectiveness of contextual approach of cooperative setting, scientific approach of cooperative setting, and problem solving approach of cooperative setting in Rectangular Flat Surface and Triangle Flat Surface Material of Clas VII studens at SMPN Accreditation A in Makassar based on (a) students’ learning achievement, (b) students’ learning activities, and (c) studens’ response. The population of the study were the entire students of class VII at SMPN Accreditation A in Makassar of academic year 2015/2016; whereas, the samples of the study were 3 school taken ramdomly which were given treatment in Mathematics learning by applying contextual approach of cooperative setting, scientific approach of cooperative setting, and problem solving approach of cooperative setting. Before learning was conducted, the pretest was given beforehand to three schools. Afterwards, learning was conducted by applying contextual approach of cooperative setting, scientific approach of cooperative setting, and problem solving approach of cooperative setting in the experiment class. The result of the study reveals that all of approaches are in fairly effective category with the effectiveness level of each approach is as follows: contextual approach of cooperative setting is E=3.42, the scientific approach of cooperative setting is E=3.20, problem solving approach of cooperative setting is E=3.32. The contextual approach of cooperative setting is more effective than scientific approach of cooperative setting, and problem solving approach of cooperative setting in Mathematics learning of class VII students at SMPN Accreditation A in Makassar